Studies on the interaction of diflunisal ion with cyclodextrins using ion-selective electrode potentiometry - Sideris, EE; Valsami, GN; Koupparis, MA; Macheras, PE (EUROPEAN JOURNAL OF PHARMACEUTICAL SCIENCES, 1999)
The interaction of diflunisal ion (DF) with beta-cyclodextrin (PCD), gamma-cyclodextrin (gamma CD), and hydroxypropyl-beta-cyclodextrin (HP beta CD) was studied in phosphate buffer, pH 7.4, at 5-37 degrees C and various CD concentrations using a home-made diflunisal ion-selective electrode. Typical direct binding plots and Scatchard plots were obtained with HP beta CD. The Scatchard model for one class of binding sites was used for the estimation of binding parameters for the DF/HP beta CD interaction. The estimates for n (number of binding sites per CD molecule) were in all cases very close to unity, indicating 1:1 complexation. The association constant (K) estimates decrease with increasing temperature. Sigmoidal direct binding plots and concave-downwards Scatchard plots were obtained with various beta CD or gamma CD concentrations. The Hill model was used for the estimation of the binding parameters for the DF/beta CD and DF/gamma CD interactions. Both the Hill coefficients and the binding constants were markedly dependent on the CD concentration. These findings indicate the cooperative character of DF/beta CD and DF/gamma CD interactions. The foe energy change, Delta G, and the thermodynamic parameters, Delta H and Delta S, were estimated for each of the interactions studied using the Van't Hoff equation. (C) 1999 Published by Elsevier Science B.V. All rights reserved.
Keywords: beta-cyclodextrin; binding; cooperative binding; diflunisal; gamma-cyclodextrin; Hill model; hydroxypropyl-beta-cyclodextrin; ion-selective electrodes; Scatchard model